Intent to migrate among nursing students in Uganda: Measures of the brain drain in the next generation of health professionals - Nguyen, Lisa; Ropers, Steven; Nderitu, Esther; Zuyderduin, Anneke; Luboga, Sam; Hagopian, Amy (2008, 2008)
There is significant concern about the worldwide migration of nursing professionals from low-income countries to rich ones, as nurses are lured to fill the large number of vacancies in upper-income countries. This study explores the views of nursing students in Uganda to assess their views on practice options and their intentions to migrate. Methods: Anonymous questionnaires were distributed to nursing students at the Makerere Nursing School and Aga Khan University Nursing School in Kampala, Uganda, during July 2006, using convenience sampling methods, with 139 participants. Two focus groups were also conducted at one university. Results: Most (70%) of the participants would like to work outside Uganda, and said it was likely that within five years they would be working in the U.S. (59%) or the U.K. (49%). About a fourth (27%) said they could be working in another African country. Only eight percent of all students reported an unlikelihood to migrate within five years of training completion. Survey respondents were more dissatisfied with financial remuneration than with any other factor pushing them towards emigration. Those wanting to work in the settings of urban, private, or U.K./U.S. practices were less likely to express a sense of professional obligation and/or loyalty to country. Those who have lived in rural areas were less likely to report wanting to emigrate. Students with a desire to work in urban areas or private practice were more likely to report an intent to emigrate for financial reasons or in pursuit of country stability, while students wanting to work in rural areas or public practice were less likely to want to emigrate overall. Conclusion: Improving remuneration for nurses is the top priority policy change sought by nursing students in our study. Nursing schools may want to recruit students desiring work in rural areas or public practice to lead to a more stable workforce in Uganda.
Keywords: Migrate; Nursing students; Uganda; Brain drain; Health professionals